USING DIGITAL RESOURCES IN TEACHING FOREIGN LANGUAGES - Abdullaeva Shakhlo Sayfievna (Western European Studies, 2024)
The landscape of foreign language learning has undergone a dramatic shift with the proliferation of digital resources. This article explores the transformative potential of these tools for advanced learners. We will delve into how digital resources can enhance vocabulary acquisition, refine listening and speaking skills, and foster a more immersive and engaging learning experience. Additionally, we will critically analyze the pedagogical considerations for effective integration of digital resources in advanced foreign language classrooms.
Keywords: Foreign language learning; Digital resources; Advanced learners; Immersive learning